Entering a gender-neutral workplace? College students' expectations and the impact of information provision - Francesca Barigozzi; José J. Domínguez; Natalia Montinari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
Although women often outperform men in school and college, they still face higher unemployment rates and lower wages when employed. Are prospective workers aware of these inequalities, or do they expect to enter a genderneutral workplace? This paper investigates college students' expectations and the effect of information provision about gender gaps in academic performance and early labor market outcomes on the two sides of the labor market. Our lab experiment comprises a questionnaire to elicit students' beliefs about academic performance and labor market inequalities, a demand-side game, and a supply-side game. In the demand-side game, subjects act as employers and are asked to hire three candidates and assign them to tasks that differ in complexity and profitability. In the supply-side game, we elicit individual willingness to compete. Information provision takes the form of feedback on the elicited beliefs. Our treatments vary the timing of the feedback: subjects in the feedback treatment received feedback before facing the other two games, while subjects in the priming and the control treatments only received feedback at the end of the experiment. First, our findings indicate that participants are largely unaware of gender gaps. Second, while information provision doesn't substantially alter employers' hiring decisions, it increases the likelihood of assigning women to challenging tasks. Third, while feedback enhances willingness to compete among job market candidates, it does not significantly alter the gender gap in competitiveness. Overall, our experiment suggests potential positive effects of information provision on women's labor market outcomes.
Keywords: D03; C91; J71; 330; Gender Gaps; Expectations; Information provision; Competition; Hiring; Task assignment